Oxide interfacial charge engineering towards normally-off AlN/GaN MOSHEMT. (October 2016) - Swain, R.; Jena, K.; Lenka, T.R.
Abstract: In this paper a detail insight into the role of oxide/barrier interfacial charges ( N ox ) for shifting the threshold voltage ( V T ) of AlN/GaN metal oxide semiconductor high electron mobility transistors (MOSHEMTs) is gained. A model is developed for V T considering all possible charges arise at different interfaces. To validate the model the proposed device is simulated by considering different insulators and N ox into account. It is very fascinating to observe that VT is highly sensitive towards change in N ox at higher oxide dimensions, whereas at lower dimensions N ox has very negligible effect. Normally-off operation can be achieved by increasing or decreasing N ox in MOSHEMT with Al2 O3 or HfO2 as gate dielectric respectively.